2020
DOI: 10.3390/su12083291
|View full text |Cite
|
Sign up to set email alerts
|

Waste Reduction in Production Processes through Simulation and VSM

Abstract: Corporate managers often face the need to choose the optimal configurations of production processes to reduce waste. Research has shown that simulation is an effective tool among those conceived to support the manager’s decisions. Nevertheless, the use of simulation at the company level remains limited due to the complexity in the design phase. In this context, the Value Stream Map (VSM)—a tool of the Lean philosophy–is here exploited as a link between the strategic needs of the management and the operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…We assessed and compared both preassembly workstations (manual and collaborative) considering different Key Performance Indicators (KPI). As developed by Bait et al [7] and Bauters et al [30], the KPI were classified into four groups:…”
Section: Assessment Of Performance Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed and compared both preassembly workstations (manual and collaborative) considering different Key Performance Indicators (KPI). As developed by Bait et al [7] and Bauters et al [30], the KPI were classified into four groups:…”
Section: Assessment Of Performance Indicatorsmentioning
confidence: 99%
“…The system developed by Eiji Toyota, named Toyota Production Systems (TPS), pioneered this waste elimination/reduction vision and has been recognized as doing more with less [5]. To identify, eliminate and prevent wasteful operations, several techniques and tools compose the LM, such as 5S workplace organization, Total Productive Maintenance (TPM), Just-In-Time (JIT), Standard Work, pull production, or Value Stream Mapping (VSM) [6,7]. LM is widely applied in industrial settings and facilitates companies' competitiveness by reducing production costs and at the same time improving working conditions [2].…”
Section: Introduction 1sinergy Between Lean Manufacturing and Ergonomentioning
confidence: 99%
“…Value stream mapping consists of all actions (both value-added and non-value-added) needed to bring a product through the production flow from the raw material to the client delivery [23,24]. VSM permits a systemic view of the value flow in the production process, identification of problems and wastes, lessons learned and continuous improvement [25]. Value stream mapping is a powerful lean tool to improve the productivity of manufacturing industries [26,27].…”
Section: Value Stream Mappingmentioning
confidence: 99%
“…Preliminary studies have proposed numerous adaptations to Lean tools -especially Value Stream Mapping (VSM) -to meet sustainable objectives in different organizations (Bait et al, 2020;Hartini et al, 2020;Hedlund et al, 2020;Lima et al, 2023;Lorenzon et al, 2019;Mubin et al, 2023;Santos et al, 2019;Texeira et al, 2021). However, despite the efforts of the authors of this study, no research was found that dealt with the application of the use of VSM in pickers' cooperatives, making this study an important contribution to the literature.…”
Section: Introductionmentioning
confidence: 99%